(untitled) (Journal of history, 2023)
The purpose of the study is to provide a historiographic analysis of the topic of Japanese prisoners of war, released and returned to Japan by 1956, and to reveal the possibilities of research. Due to the lack of accurate data on the number of Japanese prisoners of war who died and went missing on the territory of Kazakhstan, a number of humanitarian issues have not yet been resolved; on the location of their burial sites. Political issues related to the Japanese presence on the territory of the Soviet Union were also not resolved. The memoirs of many former Japanese prisoners of war, written after returning to their homeland, and the available archival documents serve as a basis for rethinking this topic. The issues of placement, service and use of the labor of Japanese prisoners of war in the IIHC camps have not been sufficiently studied in foreign and domestic historiography. This was due to the inaccessibility of declassified archival documents relatively recently — in the late 1980s and early 1990s. However, the archives contain many materials that are not available to researchers due to their confidentiality. An objective scientific study of the issues of discussion related to the stay of Japanese prisoners of war on the territory of Kazakhstan in the post-war years contributes to the improvement of the modern approach to the problem. In addition, although the subject of this study was relatively new, the level of study of the knock came to some extent. Therefore, the article analyzes the study of the history of Japanese prisoners of war arrested as a result of World War II. Keywords: Japanese prisoners of war, People’s Commissariat of Internal Affairs, historiography, repatriation, prisoner camps.